Conservation beef: options for producers - Grimmett, Hill, speaker; Unidentified speaker (Colorado State University. Libraries, 2010)
Conservation beef or “story beef” is increasingly available in the marketplace. Beef producers who are seeking additional income streams and ways to profit from good land management and animal husbandry practices may find such a niche strategy worth considering. And several small producers locally might band together in pursuing such a marketing plan.
Presented at the Fall 2010 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Collaborative Conservation in Practice: Ecosystem Services and Environmental Markets", October 5, 2010, Colorado State University, Fort Collins, Colorado. This series focused on the role of payments for ecosystem services (PES) in collaborative conservation efforts across the Western U.S. and around the world.
Hill Grimmett is the Co-Director of Be Local Northern Colorado, and founder of the Northern Colorado Food Incubator. He comes to this work with more than 35 years of experience in both the business and non-profit worlds, primarily with early-stage companies ranging from manufacturing to high-technology. As a Fort Collins resident, he is committed to helping the local food system develop depth, diversity and long-term viability. Hill is also a collaborative conservation fellow with the Center for Collaborative Conservation.
Includes recorded speech and PowerPoint presentation.
Accessibility features: Unedited transcript.
Keywords: story beef; conservation beef; marketing